A systematic review of CAD/CAM fit restoration evaluations. (21st June 2014) - Boitelle, P.; Mawussi, B.; Tapie, L.; Fromentin, O.
Summary The evolution and development of CAD/CAM systems have led to the production of prosthetic reconstructions by going beyond the use of traditional techniques. Precision adjustment of prosthetic elements is considered essential to ensure sustainable restoration and dental preparation. The purpose of this article was to summarise the current literature on the fitting quality of fixed prostheses obtained by CAD/CAM technology.